Automated Vehicle Monitoring System - Agustinus Deddy Arief Wibowo; Rudi Heriansyah (ICON-CSE, 2014)
An automated vehicle monitoring system is proposed in this paper. The surveillance system is based on image processing techniques such as background subtraction, colour balancing, chain code based shape detection, and blob. The proposed system will detect any human’s head as appeared at the side mirrors. The detected head will be tracked and recorded for further action.